1993
DOI: 10.1021/la00032a027
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polystyrene latexes by hydrodynamic and electrophoretic fingerprinting

Abstract: We report the first measurements of the new approach of hydrodynamic fingerprinting. The hydrodynamic fingerprint is the isothermal contour diagram of the hydrodynamic size as a function of pH and pX (the logarithm of the conductivity fitS/cm)). The general applications of fingerprinting are discussed, and we compare hydrodynamic fingerprints with electrophoretic fingerprints on similar systems. The electrophoretic fingerprint is the isothermal isomobility contour diagram in the pH-pX domain. Measurements are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
1

Year Published

1996
1996
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 0 publications
5
27
1
Order By: Relevance
“…Note the linear relationship between the conductivity and . This is also expected at low volume fractions, because the interesting parameter from these measurements is the conductivity increment ⌬K/K ϱ , defined as ⌬K/K ϱ ϭ ͑K/K ϱ Ϫ 1͒/, [7] where K is the suspension conductivity (at a given ) and K ϱ is the bulk electrolyte conductivity. The experimentally determined ⌬K/K ϱ as a function of ionic strength can be seen in Table 1.…”
Section: Conductivity Measurementsmentioning
confidence: 79%
See 2 more Smart Citations
“…Note the linear relationship between the conductivity and . This is also expected at low volume fractions, because the interesting parameter from these measurements is the conductivity increment ⌬K/K ϱ , defined as ⌬K/K ϱ ϭ ͑K/K ϱ Ϫ 1͒/, [7] where K is the suspension conductivity (at a given ) and K ϱ is the bulk electrolyte conductivity. The experimentally determined ⌬K/K ϱ as a function of ionic strength can be seen in Table 1.…”
Section: Conductivity Measurementsmentioning
confidence: 79%
“…The accuracy of the conductivity increment determination is about Ϯ0.15, because three parameters must be measured to evaluate ⌬K/K ϱ , as can be seen from Eq. [7]. Finally, it should be mentioned that all conductivity measurements were made on the aged latex.…”
Section: Conductivity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fingerprinting (6)(7)(8), a means of representing colloidal variables as a function of pH and the log of the conductivity, pλ, was conceived at the University of Massachusetts in 1986. The conductivity is expressed in units of microsiemens per centimeter, which is convenient as it places the zero close to the conductivity of pure distilled water.…”
Section: Introductionmentioning
confidence: 99%
“…The conductivity is expressed in units of microsiemens per centimeter, which is convenient as it places the zero close to the conductivity of pure distilled water. Rowell and co-workers (6)(7)(8) have suggested that the solution conductivity is the experimental analogue to the ionic strength. It has the advantage of being a measured quantity that does not depend on a knowledge of the ions present in solution.…”
Section: Introductionmentioning
confidence: 99%